Entrepreneurial Management Strategy on the Management and Investment of Education Funds in Educational Institutions - Ulfa Qomariatul Jannah (Khatulistiwa Insight: Islamic Education and Learning, 2026)
This study aims to analyze the entrepreneurial management strategy in the management and investment of educational funds at the Mambaul Ulum Besuk Foundation. The research focuses on the application of entrepreneurial principles as an effort to enhance financial independence, the effectiveness of fund management, and the sustainability of the educational institution. Using a qualitative approach with a case study design, this research involves data collection techniques such as in-depth interviews, observations, and documentation. The main informants in this study consisted of the school principal, teachers, employees of the bakery business unit, and parents involved directly in the management and utilization of educational funds. The results of the study show that the application of entrepreneurial management strategies through the utilization of business units as an alternative source of funding has improved financial transparency, budget efficiency, and stakeholder trust. Additionally, the investment pattern of educational funds, which focuses on productivity and sustainability, has a positive impact on the improvement of service quality and the performance of the educational institution. The implications of this study show that the integrated and professional application of entrepreneurial management can be an effective strategy in supporting the sustainability and competitiveness of educational institutions. This research also contributes to enriching the perspective of financial management in education by placing entrepreneurship as a strategic approach in the management and investment of educational funds.